Le chronotope du salon dans quelques romans de mœurs parisiens (1860-1900) - Gabrielle Melison-Hirchwald (Itinéraires)
In the Parisian novel of manners of the second half of the nineteenth-century, as place of sociability, the drawing-room provides a fertile meeting ground where the private space of home is thrust onto the public stage. The salon chronotope furnishes the possibility to expose bourgeois speech and manners. Finally, as a mixed place, this room gives the opportunity to feminine characters to play an important role in politics in an underhand way.